Relationship between Systolic and Diastolic Blood Pressure Loads on ABPM and BMI Percentiles in Children - Chinmayi Savithru Sharma; Navneet K Venugopal; Shivaiah Balachandra (Journal of Blood Pressure, 2024)
Ambulatory blood pressure monitoring is widely used in pediatric patients to identify hypertension and its complications. Previous studies correlating obesity and hypertension using ABPMs showed increasing blood pressure loads with increasing BMI. However, BMI percentiles are more reliable indicators of obesity in children. Our study aimed to describe the association between BMI percentiles and systolic and diastolic blood pressure load using ABPM in children and adolescents. Retrospective analysis of ABPMs (Welch Allyn) was performed on a total of 115 patients between 7 and 18 years of age who were referred for elevated BP without a diagnosis of hypertension at our institution from Jan 2011 to Oct 2013. Patients were divided into 4 groups based on BMI percentile: <94th percentile, 94–98th percentile, 98–99th percentile, and >99th percentile. Analysis between blood pressure loads and BMI percentiles revealed greater mean systolic and diastolic loads with increasing BMI percentiles, but the P value was not statistically significant. Analysis of the systolic loads between children from different racial backgrounds revealed higher values in African American children than in Hispanic and Caucasian children, but the P value was not statistically significant.
Keywords: Ambulatory blood pressure monitoring (ABPM)